Alleviate Cellular Congestion Through Opportunistic Trough Filling - Yichuan Wang; Xin Liu (EAI Endorsed Transactions on Wireless Spectrum, 2014)
The demand for cellular data service has been skyrocketing since the debut of data-intensive smart phones and touchpads. However, not all data are created equal. Many popular applications on mobile devices, such as email synchronization and social network updates, are delay tolerant. In addition, cellular load varies significantly in both large and small time scales. To alleviate network congestion and improve network performance, we present a set of opportunistic trough filling schemes that leverage the time-variation of network congestion and delay-tolerance of certain traffic in this paper. We consider average delay, deadline, and clearance time as the performance metrics. Simulation results show promising performance improvement over the standard schemes. The work shed lights on addressing the pressing issue of cellular overload.